2021
DOI: 10.1108/jic-02-2020-0057
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the history and trends of “The Journal of Intellectual Capital”: a bibliometrics, altmetrics and text mining analysis

Abstract: PurposeThe Journal of Intellectual Capital (JIC) celebrated its 20th anniversary in 2020. Therefore, the present study aims to provide a general overview of the history and key trends in this journal during 2000–2019.Design/methodology/approachTwo types of citation and textual data during a 20-year journal period were retrieved from the Scopus database. The citation structures and contents were explored based on a combination of bibliometric analysis, altmetric analysis and text mining. The journal themes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 150 publications
(206 reference statements)
0
3
0
Order By: Relevance
“…[6] upgrade use asset no form allows the company for having high profitability _ without increasing their capital investment. Result research [7] states that implication from trend study time front required for understanding how Intellectual Capital concept can be applied for expanding the limits with To do things like finding an answer on " how " question rather than " what " question. This is a reason other researchers for reflecting on how is Intellectual Capital recognized in MSMEs with their Intellectual Capital.…”
Section: Introductionmentioning
confidence: 99%
“…[6] upgrade use asset no form allows the company for having high profitability _ without increasing their capital investment. Result research [7] states that implication from trend study time front required for understanding how Intellectual Capital concept can be applied for expanding the limits with To do things like finding an answer on " how " question rather than " what " question. This is a reason other researchers for reflecting on how is Intellectual Capital recognized in MSMEs with their Intellectual Capital.…”
Section: Introductionmentioning
confidence: 99%
“…Bibliometric analysis is a tool for quantitatively describing, evaluating, and monitoring the evolution of the scientific realm under study based on the statistical analysis of bibliographic material [27]. Due to the utility of this type of analysis in exploring large volumes of scientific data and generating high research impact [28], bibliometric studies have gained immense popularity across different areas of business and management such as business model [29,30], intellectual capital [31], entrepreneurship [32,33], dynamic capabilities [34], and operations [35]. Traditional review methods such as qualitative techniques for structured literature review are often timeconsuming and prone to researchers' subjective bias [27], so we prefer to not use them in this study aimed at exploring a vibrant area with a large number of pieces of research and giving an objective and informative view about this extensive research.…”
Section: Introductionmentioning
confidence: 99%
“…Dabi c et al (2021 were able to cluster the IC articles published during the last 20 years (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019) in the Journal of IC into two five groups: (1) human capital and innovation; (2) IC strategic management in universities; (3) IC, disclosure and reporting; (4) IC, innovation and value analysis and finally (5) innovation. Considering also the 2000-2019 period, the outcomes of Givi et al (2022) from text mining of the abstracts of selected articles from the Journal of Intellectual Capital, showed that, during the period of analysis, the main topics tacked by publications were "measurement", "financial performance" and "IC reporting".…”
Section: Introductionmentioning
confidence: 99%